The race for global leadership and its risks for world instability: Technologies of controlling and mitigation - Guo, Xiaoqing; Chmutova, Iryna; Kryvobok, Kateryna; Lozova, Tetiana; Kramskyi , Serhii (Research Journal in Advanced Humanities, 2024)
In today's ever-evolving geopolitical landscape, the pursuit of global leadership has become an intensifying competition that holds significant implications for global stability. This article explores the emergence of rivalry among major global powers as well as existing and potential consequences it poses for the world. Taking into account the shifting dynamics in international relations, the article highlights the primary contenders vying for global leadership and their distinct approaches to exerting influence on the world stage. It scrutinizes the escalating tensions between these powers as they strive to secure technological, economic, and military superiority, and how these rivalries can reverberate across different regions. The article examines the impact on international cooperation efforts, as rivalries may hinder collaboration on critical global issues such as climate change, security, and governance. Additionally, the study assesses the economic interdependency among nations and the potential disruptions that can arise as rival powers aim to shape the global order to their advantage. Addressing the potential consequences of this rivalry, the research explores into the risks of military escalation and arms races, highlighting the need for diplomatic efforts to mitigate conflict and promote peaceful resolutions. It also emphasizes the importance of fostering multilateral institutions and mechanisms for effective conflict resolution and cooperation among nations. The study presents relevant strategies to control and mitigate the risks associated with global instability.